Transport beyond oil : policy choices for a multimodal future - Renne, John L.; Fields, Billy (Island Press, 2013)
"Seventy percent of the oil America uses each year goes to transportation. In Transport Beyond Oil, leading experts show how to slash that statistic and reduce our dependence on fossil fuels. The authors demonstrate that smarter development and land use decisions, paired with better transportation systems, can dramatically lower energy consumption. John Renne calculates how oil can be saved through a future with more transit-oriented development. Petra Todorovitch examines the promise of high speed rail. Peter Newman envisions 100% oil-free cities through the development of electric-transit, renewable natural gas, and other sustainable energy sources. Additional topics include funding transit, freight transport, and non-motorized transportation systems. Each chapter provides policy prescriptions and their measurable results. Transport Beyond Oil delivers practical solutions, based on quantitative data. This fact-based approach offers a new vision of travel that is both transformational and achievable" --Provided by publisher.